The Influence of Product Quality and Electronic Word of Mouth on Purchasing Decisions at Dessert Box Bittersweet by Najla - Fini Fitriya Handayani; Suryari Purnama (PT FORMOSA CENDEKIA GLOBAL, 2023)
The research objective was to determine the effect of product quality and electronic word of mouth on purchasing decisions at the Bittersweet by Najla dessert box. The population of this study are active followers of the Bittersweet by Najla Instagram account. This study uses a non-probability sampling method using purposive sampling technique, instrument testing uses validity, reliability and classical assumption tests. This study uses the method of Multiple Linear Regression Analysis. The results showed that product quality and electronic word of mouth had a positive and significant effect on purchasing decisions. Then the quality of the product and electronic word of mouth together influence the purchasing decision at the Bittersweet by Najla dessert box. This means that the better the quality of the product, the better the talk on social media which can improve purchasing decisions